Analisis Fungsi Kepemimpinan pada Divisi Garmen Perusahaan Tekstil di Kabupaten Bandung - Moch. Nizar Zaelani; Ester Manik (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
This research conduct to know the description of the leadership function in the Garment Division. It is using descriptive analysis to find out how the leadership function describes. Respondents are employees of 40 people. Based on the calculation, it knows that the leadership function is quite good. However, to improve the leadership function, it can be considered in connection with the results of the research, which is to establish better communication between the leader and their subordinates furthermore, for the organization to distribute work tasks following its employees' work abilities so that they can complete tasks on time.